EUROPEAN GUIDEBOOKS AS A GENRE OF TOURISM DISCOURSE: HISTORICAL OVERVIEW AND MODERN CLASSIFICATION - Didkovska, Tetiana (International Journal of Innovative Technologies in Social Science, 2023)
The article studies the formation of the travel guidebook as a genre of tourism discourse, whose key features are a high degree of generalization, the accuracy of information, impersonality and persuasion. The tourist guide is an applied genre and also a cultural representation of the past of a city or region. Moreover, the guidebook is a historical object, which can say a great deal about both the destination that it describes and the culture in which it is made, as well as the values of society in the period when it was written. The main stages of the genre development are researched on the material of specific printed guidebooks.  Particular attention is paid to European guidebooks. The article highlights some socio-cultural peculiarities that influence the development of the genre. The paper also provides the classification of modern tourist guidebooks and shows their changing role in the digital era. While more people report using the Internet for travel, guidebooks are still rated as the most influential source of information by travellers. The findings suggest that both the uses and the value types of guidebooks are related to emerging information communication technologies.